A clinical study on dyselectrolytemia and changes in renal function in patients with 25% to 60% flame burn injury - Mohanty, Upasana; Dhar, Pinak Pani; Patar, Dipankar (International Surgery Journal, 2021)
Background: Severe fluid loss is the greatest problem faced following major thermal burn injuries accompanied by changes in the level of electrolytes. Standard fluid resuscitation derived from Parkland’s formula and body’s response to it is measured in terms of correction of dyselectrolytemia and urine output. Methods: A prospective cross sectional study involving 80 patients were included in the study with male patients being 28 and females being 52. Flame burns involving ≥25% - ≤60% of BSA presenting within 24 hours of flame burn injury were taken into account. Serial follow up of serum electrolytes was done on the day of presentation, day 2, day 3 and day 7 its effect on standard fluid resuscitation was studied. Results: Renal function is indirectly related to the percentage of flame burn, hence decreasing urine output and linear increase in serum creatinine is suggestive of increased surface area of burn. The mean serum sodium on the day of admission was roughly normal whereas as the days progressed there was significant hyponatremia with normalisation of day 7, whereas serum potassium was initially normal followed by hyperkalemia. Conclusions: An initial assessment involved calculation of percentage of total body surface area burn injury followed by of estimation of fluid requirement according to standard Parkland formula. Monitoring of electrolyte imbalance was noted for 2nd, 3rd and 7th day of hospitalisation. Derangements in these parameters were observed during course of admission followed by normalisation on the 7th day.